Rheological properties of isotropic magnetorheological elastomers featuring an epoxidized natural rubber. (16th September 2016) - Yunus, Nurul Azhani; Mazlan, Saiful Amri; Ubaidillah,; Choi, Seung-Bok; Imaduddin, Fitrian; Abdul Aziz, Siti Aishah; Ahmad Khairi, Muntaz Hana
Abstract: This study presents principal field-dependent rheological properties of magnetorheological elastomers (MREs) in which an epoxidized natural rubber (ENR) is adopted as a matrix (in short, we call it ENR-based MREs). The isotropic ENR-based MRE samples are fabricated by mixing the ENR compound with carbonyl iron particles (CIPs) with different weight percentages. The morphological properties of the samples are firstly analysed using the microstructure assessment. The influences of the magnetic field on the viscoelastic properties of ENR-based MREs are then examined through the dynamic test under various excitation frequencies. The microstructure of MRE samples exhibits a homogeneous distribution of CIPs in the ENR matrix. The dramatic increment of storage modulus, loss modulus and loss tangent of the ENR-based MREs are also observed from the field-dependent rheological test. This directly demonstrates that the stiffness and damping properties of the samples can be adjusted by the magnetic field. It is also seen that the CIP content, exciting frequency and the magnetic field essentially influence the dynamic properties of the ENR-based MREs. The strong correlation between the magnetization and the magneto-induced storage modulus could be used as a useful guidance in synthesizing the ENR-based MREs for certain applications.